Pemanfaatan Limbah Cangkang Pala Untuk Meningkatka Nilai Tambah Ekonomi Value_Added Innovation - Arga Ramadhana; Reski Rahman Sriwijaya (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Fakfak Regency is one of the nutmeg production centers in Eastern Indonesia, but the utilization of nutmeg shell waste, a byproduct of this commodity, has not been optimal. To date, nutmeg shell waste has been discarded or burned without further processing, leading to environmental problems and loss of economic potential. This community service project aims to assess the potential use of nutmeg shell waste as a raw material for value-added products and to analyze the potential economic impact for the local community. The methods used include training nutmeg farmers on utilizing nutmeg shell waste. These include: 1. Conducting focus group discussions (FGDs) with farmers to address the problems they face, 2. Conducting training and technology transfer, 3. Mentoring and monitoring nutmeg shell utilization, and evaluating and providing feedback on the results of the training on nutmeg shell waste utilization. This aims to increase farmers' knowledge in utilizing nutmeg shell waste, which can have high economic value.